Study Progression of Apelin/APJ Signaling and Apela in Different Types of Cancer - Liu, Longfei; Yi, Xiaoping; Lu, Can; Wang, Yong; Xiao, Qiao; Zhang, Liang; Pang, Yingxian; Guan, Xiao (Frontiers in Oncology, 2021)
Apelin is an endogenous ligand that binds to the G protein-coupled receptor angiotensin-like-receptor 1 (APJ). Apelin and APJ are widely distributed in organs and tissues and are involved in multiple physiological and pathological processes including cardiovascular regulation, neuroendocrine stress response, energy metabolism, etc. Additionally, apelin/APJ axis was found to play an important role in cancer development and progression. Apela is a newly identified endogenous ligand for APJ. Several studies have revealed the potential role of Apela in cancers. In this article, we review the current studies focusing on the role of apelin/APJ signaling and Apela in different cancers. Potential mechanisms by which apelin/APJ and Apela mediate the regulation of cancer development and progression were also mentioned. The Apelin/APJ signaling and Apela may serve as potential therapeutic candidates for treatment of cancer.